A STUDY OF DIFFERENCE BETWEEN ACHIEVEMENT MOTIVATION OF ATHLETE OF CENTRAL BOARD OF SECONDARY EDUCATION AND CBSE PRIVATE SCHOOLS OF NAGPUR CITY - Joarder, Saikat Subhash; V. B. Datarkar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The evolution of human physical activity and its relationship with motivation have been pivotal throughout history. Ancient societies thrived on physical prowess, with leaders often epitomizing physical fitness. However, the advent of machinery and modern conveniences has led to a decline in physical activity levels among later generations. Despite this, the innate propensity for movement remains inherent in human nature, especially evident in childhood. This paper explores the concept of achievement motivation within the context of sports psychology, emphasizing its significance in understanding human behavior and performance. By examining existing literature, particularly the study by Sylvain Laborde et al. (2016) on positive personality traits in athletes, the importance of motivation in sports performance becomes evident. This study aims to investigate the achievement motivation of male athletic players within the Central Board of Secondary Schools in Nagpur city. The significance of this research lies in its potential to enhance understanding of achievement motivation among athletes and its implications for training and performance. However, certain limitations, such as external factors influencing participants’ behaviors, must be considered. The research methodology involves qualitative techniques, primarily utilizing surveys and standardized questionnaires. The analysis focuses on the Sports Achievement Motivation Test to categorize participants’ motivation levels. The findings indicate a predominantly low sports achievement motivation among the sampled male athletes, highlighting the need for further investigation into motivational factors affecting sports performance. This study contributes to the growing body of research in sports psychology and provides valuable insights for educators, coaches, and athletes striving for improved performance.